A new method to retrieve spectral absorption coefficient of highly-scattering and weakly-absorbing materials. (March 2016) - Dombrovsky, Leonid A.
Abstract: A significant uncertainty in the absorption coefficient of highly scattering dispersed materials is typical in the spectral ranges of very weak absorption. The traditional way to identify the main absorption and scattering characteristics of semi-transparent materials is based on spectral measurements of normal-hemispherical reflectance and transmittance for the material sample. Unfortunately this way cannot be used in the case of in vivo measurements of optical properties of biological tissues. A method suggested in the present paper is based on thermal response to the periodic radiative heating of the open surface of a semi-transparent material. It is shown that the period of a variation of the surface temperature is sensitive to the value of an average absorption coefficient in the surface layer. As a result, the monochromatic external irradiation combined with the surface temperature measurements can be used to retrieve the spectral values of absorption coefficient. Possible application of this method to porous semi-transparent ceramics is considered. An example problem is also solved to illustrate the applicability of this method to human skin. The approach suggested enables one to estimate an average absorption coefficient of human skin of a patient just before the thermal processing. Highlights: Transient radiative-conductive heat transfer in scattering media. Periodic laser-induced heating of a weakly-absorbing medium. Identification of absorption coefficient from the experimental data. Possible use of novel method in solar engineering and biomedicine.